Victim, Police, and Prosecutorial Responses to Same-Sex Intimate Partner Violence: A Comparative Approach - Lantz, Brendan (Journal of contemporary criminal justice, 2020)
Research on intimate partner violence (IPV) and the criminal justice response to such incidents is extensive, but the majority of this research has focused on IPV perpetrated by men against women in heterosexual partnerships. Yet, recent research has indicated that the prevalence of IPV among LGB (lesbian, gay, and bisexual) individuals may be as high as or higher than that of the general population. At the same time, a significant body of research has examined police and prosecutorial responses to IPV; again, the overwhelming majority of this research has also focused on heterosexual partners. Following this, the current research uses National Incident-Based Reporting System (NIBRS) data to create dyads of both opposite-sex (i.e., male-female and female-male) and same-sex partners (i.e., male-male and female-female) to investigate the joint relationship between sex, sexual orientation, and three different criminal justice outcomes: victim refusal to cooperate with police, police decision to arrest, and the prosecutorial decision to deny a case.